Evaluasi Hasil Belajar Siswa pada Proses Pembelajaran menggunakan Metode Problem-Based Learning - Hendri Saputra; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research aims to review student learning outcomes using the Problem-based learning (PBL) method in the Basics of Electrical Engineering subject in class X TITL 1 SMK Negeri 5 Padang. This research is quantitative research using the Pre-Experimental Design method, The One Shot Case Study type. The subject of this research is class X TITL 1 SMK Negeri 5 Padang. The research instrument consists of evaluation questions in the form of objective, essay, matching, true and false and labeling. Based on the results of the posttest carried out, there were 87.5% of students completed it with the average student achieving the learning objective criteria >75, namely 79.85 and the average student who did not complete it was 30.21, so it can be concluded that the PBL method can improve student learning outcomes.